Taxa Of Family Fabaceae: A Potential Of Local Medicinal Values In Vindhya Region Uttar Pradesh, India - RICHA SINGH CHAUDHARY (International Journal of Pharma and Bio Sciences, 2010)
The Vindhya region of Uttar Pradesh includes Mirzapur and Sonbhadra districts, which is mostly covered with forest. During exploration of this region we collected 51 species of 35 taxa is belonging to the family Fabaceae. Among these species an account of 23 ethno-medicinal information which is traditional used by tribes like Gond, Kols, Mushar, Baiga & Nutts from this region and 19 species are used as medicines in the welfare of the people. The ethno-medicinal uses, disease, localities and field numbers has been provided in this paper.